Bruce Bechtol, The Last Days Of Kim Jong-Ii: The North Korean Threat in a Changing Era - Tan, Er-Win (Malaysian Journal of International Relations, 2015)
The abstract is not available. To access, please order the printed version or browse the electronic version of this article.